PENGARUH KUALITAS AUDIT, DEBT DEFAULT, OPINION SHOPPING, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR (Yang Terdaftar DiBursa Efek Indonesia 2011-2015) - Vita Mustika; Hardi '; Julita ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Responsibility of auditors currently do not only focus on assessing the fairness of financial statements and detecting fraud, but also information that is not limited in the things revealed in the financial statements, such as disclosure of information about the existence and continuity of corporate entities. This is due to the demands of the shareholders to the auditor ti provide early warning about the prospect of a company as consideration before deciding on an investment decision. In this study, we attempt empirically to examine the effect of audit quality, debt default, opinion shopping, and company’s growth on receiving a going concern audit opinion of a compaany. Research sample amounts to 20 companies selected with purposive sampling method, with observation period of 5 years.The date used were secondary data. The data that used in this research is audited financial statements that published by manufacturing companies listed at Indonesian Stock Exchange from 2011-2015. The method of analysis used logistic regression method. The result of logistic regression using SPSS that, audit quality weren’t significant with going concern opinion. Variables debt default, opinion shopping, and growth of company’s weren’t significant with going concern opinion.Keyword: Audit Quality, Debt Default, Opinion Shopping, Growth Companies, Going Concern.